Para‐ortho hydrogen conversion: Solving a 90‐year old mystery. Issue 1 (12th January 2021) - Zhang, Xia; Karman, Tijs; Groenenboom, Gerrit C.; van der Avoird, Ad
Abstract: Almost ninety years have passed since the experiments of Farkas and Sachsse [Z. Phys. Chem. B 1933; 23:1] on para‐ortho hydrogen conversion catalyzed by paramagnetic species such as O 2, but a detailed and quantitative understanding of the conversion process and its temperature dependence was still lacking. Here, we present a complete and quantitative theoretical treatment of this catalytic process. Both interactions causing the conversion are included: the magnetic dipole‐dipole coupling between the electron spin of O 2 and the nuclear spins in H 2 and the Fermi contact coupling from spin densities at the H‐nuclei induced by O 2 . The latter were extracted from ab initio electronic structure calculations. State‐to‐state conversion cross sections and rate coefficients are obtained from quantum mechanical coupled‐channel calculations including the full anisotropic O 2 ‐H 2 interaction potential and by treating both the spin‐dependent couplings perturbatively. The total rate coefficient agrees with the experimental value recently measured by Wagner [Magn. Reson. Mater. Phys., Biol. Med. 2014; 27:195] in O 2 ‐H 2 gas mixtures and explains the temperature dependence observed in the 1933 measurements mentioned above. Key points: two species of hydrogen, para and ortho conversion finally explained by ab initio theory para‐hydrogen induced polarization in NMR and MRI Abstract : First‐principles quantum calculations finally explain how para‐ortho hydrogen conversion is catalyzed by paramagnetic molecules.